Kırsal Peyzajdaki Değişim Üzerinden Soylulaştırmayı Okumak: Yunt Dağı Örneği (Manisa) - Ferhat Arslan; Cengiz Gürbıyık; Yasin Furkan Şenlik (Coğrafi Bilimler Dergisi)
This study aims to determine the rural gentrification process in Yunt Mountain, which is located in a between İzmir and Manisa provinces and is an important geographical value with its physical and human geography elements. Within the scope of the study, the phenomenon of gentrification was examined by revealing the change in the rural landscape in the case of 11 villages on Yunt Mountain. In the study, where fieldwork was used as the main research method, field surveys were carried out in various periods between 2019 and 2024. The data obtained were transferred to the map with ArcGis 10.8.1 software and the study was visualised with a rich photo archive. After the study, it was determined that the land and housing prices in the neighbourhoods taken as a sample have risen to a level to compete with the city centre, the newly built houses are built with additions that are not suitable for the structure of the rural area and there are visible problems in land use. It is concluded that this situation, even if not in a total manner in the field, especially in some villages (Bağyurdu, Gülbahçe, Üçpınar), the process of gentrification has progressed rapidly